The Effect of Woman's Work on Alimony between Jurisprudence and Law - Nada, Aziz Ali (Journal of Islamic Sciences, 2019)
I attempted in this research to indicate the impact of woman's work on the alimony that is given to her according to the regulations of jurisprudence and law. I employed the inductive, deductive and comparative analytical approach. The research has been divided into seven research topics and has reached the following conclusions:1- In both Sharea' and civil law, the woman's alimony is a responsibility of the father until she marries, and that the wife's alimony is the responsibility of her husband because she is linked to him.2- The woman can spend her money as she wishes as she is financially independent and no one can dominate her.3- Texts of both jurisprudence and law affirm the legality the work of the woman in certain fields and according specific standards.4- If the woman goes to work after her husband permits her to do so,, she then deserves alimony, but if he disagrees and does not grant his wife such a permission, he is not therefore required to pay her any alimony.5- The woman can o require her husband to agree that she stays at work if she has been working.6- The working woman has financial responsibilities, but these responsibilities are not a must according to Shara', but the woman can friendly do them as a sign of loyalty and as an indicator of the good relationship between her and her husband. Of these responsibilities is spending on herself, her house and her children in case the husband asks for this or if he is financially in need for help from his wife. However, law does not explicitly refer to such a case.
Keywords: Woman's work; Wife's alimony; Female's alimony